Peran APEC Dalam Perekonomian Indonesia Sebagai Negara Berkembang - novita diana lestari (LP4MK STKIP PGRI Lubuklinggau, 2021)
This article aims to determine Indonesia's international relations with APEC, which is viewed from the role of APEC in Indonesia's economy as a developing country. The method used in this article is literature study, namely research that uses references to scientific journals and books. APEC is an international organization in the economic field that was formed due to problems caused by the cold war.. In its membership, Indonesia also takes part in the High Level Conference which is held annually. Indonesia's biggest role is to host the APEC Summit held in Bogor and then produce the Bogor Goals. APEC provides funding for projects that support economic capacity building and community welfare, this is an impetus for developing APEC member countries such as Indonesia to further enhance competitiveness and economic growth.